Analisis Semiotika Menurut Ferdinand De Saussure terhadap Petanda dan Penanda Nilai Nilai Pancasila - Vanesa, Lusia Gita; Manullang, Delima Br; Nadine, Syahiba; Natalia, Rismauli; Ameria, Cristin; Yunita, Sri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The purpose of this research is to examine the values ​​contained in Pancasila using Ferdinand de Saussure's semiotic approach, with a particular emphasis on the relationship between signifiers and signifieds. This research was conducted using a qualitative descriptive approach and library research techniques. Data were obtained from various literature related to semiotic theory and the concept of Pancasila. The formulation of the five principles of Pancasila, considered a sign system, is the subject of this research. The study shows that values ​​such as divinity, humanity, unity, democracy, and social justice function as signifiers, while the texts and symbols of Pancasila serve as signifieds. Social consensus and Indonesian history determine the relationship between the two. Therefore, Pancasila functions not only as the foundation of the state but also as a series of symbols that convey shared meaning and shape national identity.